Pendampingan Penerapan Model Pembelajaran Flipped Classroom Berbasis Digital bagi Guru di SMKS Budi Dharma Kota Dumai - Johari Afrizal; Rugaiyah Rugaiyah; Akhmar Efendi; Intan Syazwina Salsabila (Jurnal Pengabdian UNDIKMA, 2023)
This community service activity aims to assist teachers at SMKS Budhi Dharma in the city of Dumai in applying the digital-based flipped classroom learning model. The implementation of this service used the mentoring method, which included providing material, demonstrations, training, and mentoring, as well as evaluating this activity using a questionnaire and analyzing descriptively. The results of this service showed that teachers at SMKS Budi Dharma could apply the Flipped Classroom learning model, distribute learning content, and gave assignments online through the Google Classroom and Socrative applications. It is hoped that in the future, teachers at SMKS Budi Dharma can use information technology tools provided by the school on an ongoing basis to improve the quality of learning.